THE EFFECTIVENESS OF HANDS ON AND MINDS ON STUDENT WORKSHEET ON CELL MATERIAL TO TRAIN THE SCIENTIFIC PROCESS SKILLS OF XI GRADE - Shinta Dwi Martika; Widowati Budijastuti (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2018)
Scientific process skills need to be mastered by students to strengthen the knowledge and understandingthe scientific theories and concepts. Hands on and minds on is an appropriate approach to trained thescientific process skills. This research aimed to describe the effectiveness of Hands On and Minds Onstudent worksheet on Cell material to train the scientific process skills of XI grade. This research was adevelopmental research which used the 4D development model (Define, Design, Develop andDiseminate). But, in this study carried out only until the stage of development (develop) and not doingdisseminate (disseminate). The trial of this research was implemented to 20 students of SMA Negeri 1Prambon in April-May 2018. The effectiveness of this worksheet which reviewed from test result andstudents‟ responses showed very good with the students' average score percentage mastery in scientificprocess skills is 100% and 90.45% of students responded positively. Based on the data, it can beconcluded that Hands On and Minds On student worksheet on Cell material to train the scientific processskills of XI grade is effective so it can be used in the teaching and learning process.Keywords: Effectiveness, Hands On, Minds On, Scientific Process Skills, Cell Material.